The whole truth : the hidden agendas behind decades of health misinformation--and what to do about it - Campbell, T. Colin, 1934-; Campbell, Nelson (BenBella Books, Inc, 2026)
"In a compelling new analysis, T. Colin Campbell, coauthor of The China Study and author of the New York Times bestselling follow-up, Whole, brings to light a series of first-hand experiences that starkly demonstrate how corporate influence in academia, government and the media determines-and sometimes actively suppresses-public access to nutrition research. With an eye-opening look behind-the-scenes of nutrition policy, The Whole Truth maps out an alarming pattern that amplifies institutionally backed "standards of health" while suppressing substantial information on natural, nutritional alternatives"-- Provided by publisher.